2018
DOI: 10.20546/ijcrar.2018.609.010
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Indigenous Knowledge Systems in Agriculture for Climate Change Adaptation and Mitigation in Southeast Nigeria

Abstract: Article Info This study was carried out to analyze indigenous knowledge practices employed by farmers for climate change adaptation and mitigation by farmers in Southeast Nigeria. A total of 360 farmers were randomly selected from 3 states of Southeast, Nigeria. Questionnaires and oral interview were used to elicit information from the respondents. Mean and Standard deviation were used to analyze data collected. Results showed that the famers were fully aware of climate change variability as indicated by a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Another crucial conclusion drawn from this study is that farmers understand the concept of climate change and its impacts on their livelihoods, and based on that they use their (Dove, 2000;Sillitoe, 2007;Gerke and Ehlert, 2011;Chikaire and Nnadi, 2011;Soh and Omar, 2012;Enns, 2015). The study demonstrated that the neglect of Also, in this study the challenges of applying climate change adaptation was discussed but the topic was not exhausted and there is therefore the need for further research into the challenges of using indigenous knowledge and how the challenges can be addressed.…”
Section: Adaptationmentioning
confidence: 84%
See 2 more Smart Citations
“…Another crucial conclusion drawn from this study is that farmers understand the concept of climate change and its impacts on their livelihoods, and based on that they use their (Dove, 2000;Sillitoe, 2007;Gerke and Ehlert, 2011;Chikaire and Nnadi, 2011;Soh and Omar, 2012;Enns, 2015). The study demonstrated that the neglect of Also, in this study the challenges of applying climate change adaptation was discussed but the topic was not exhausted and there is therefore the need for further research into the challenges of using indigenous knowledge and how the challenges can be addressed.…”
Section: Adaptationmentioning
confidence: 84%
“…Several authors acknowledge the pivotal role of indigenous knowledge in development especially in sustainable resource use (Bronkensha et al 1980;Warren, 1990;Agrawal, 2005;Antweiler, 1998, Gerke andEhlert, 2011;Chikaire and Nnadi, 2011;Soh and Omar, 2012;Enns, 2015). Indigenous knowledge is important for development because it is the resource that provides the avenue for local people especially the poor to evolve strategies to solve their problems so as to enhance their living conditions (livelihoods).…”
Section: Indigenous Knowledgementioning
confidence: 99%
See 1 more Smart Citation